Response to 'Cutaneous eruptions associated with haematological malignancies: the need for a unifying nomenclature'. (4th March 2019) - Visseaux, L.; Durlach, A.; Barete, S.; Ingen‐Housz‐Oro, S.; Ortonne, N.; Grange, F.
Abstract : Linked article: R. Maglie et al. J Eur Acad Dermatol Venereol 2019;33 : e191–e192.https://doi.org/10.1111/jdv.15452